Diagnóstico comunitario de salud del Barrio Chirimoyo, septiembre-diciembre de 2013 - Alvarado Maldonado, Silvia Anabel (2013)
The present study titled " DIAGNOSIS COMMUNITY HEALTH DISTRICT cherimoya , SEPTEMBER- DECEMBER 2013 " is framed in the macro - project entitled NURSING PARTICIPATION MODEL OF COMPREHENSIVE HEALTH CARE - MAIS HOSPITAL UNIVERSITY Motupe SEPTEMBER- DECEMBER 2013 which buscacontribuir social development of the town , bringing with statistical data that will enable them to basic health teams Motupe University Hospital , develop strategies for maintaining and improving the health of individuals , families and communities from a biopsychosocial , multidisciplinary and intercultural approach. This study is descriptive as facts and characteristics related to population and environment is detailed , the instrument for data collection was the family record compiled by the MSP to which I add a container primer necessary information all this being annexed for examination and thus obtain the district 's own results. The Quarter is distributed Chirimoyo 27 families and 110 inhabitants. The age group 20 to 64 years together with a prevalence of females in the population. His education is maintained at a basic level . The occupation of the inhabitants is based on agriculture and livestock . In the 27 families there consuming unsafe water , poor sewage and garbage disposal , and hence poverty poor housing conditions , unemployment or informal employment of the household head and overcrowding. As for the epidemiological profile Hypertension is prevalent in chronic degenerative population followed by the Diabetes disease and a school was also identified with intellectual disabilities. Keywords : Community health diagnosis Neighborhood Chirimoyo and results.